The Unexpected and Education: Curriculums for Creativity - Elisondo, Romina Cecilia (2013)
We propose ourselves to argue about the importance of creating unexpected contexts as a strategy to promote creative processes in education. We have analyzed educational proposals by our team research and specialists’ theoretical issues in the field of education and creativity. Our intention is to present theoretical and practical considerations about the role of the unexpected in the promotion of creativity in educational contexts. Learning activities, teachers, contexts, materials and teacher intervention are some of the components of educational contexts that can be designed in an unexpected way to give place to situations for creativity.